ANALISIS RASIO LIKUIDITAS TERHADAP KINERJA LAPORAN KEUANGAN KOPERASI PEGAWAI BANK TABUNGAN NEGARA CIREBON - Rusto Nawawi; Endah Budiastuti; Ardhi Fajriansyah (FEB Institut Bakti Nusantara, 2022)
Financial overall performance is an outline of the economic circumstance of a enterprise that's analyzed with economic evaluation tools. In assessing the enterprise`s economic overall performance, a sure degree or benchmark may be used. Usually the degree used is the ratio. The motive of this look at become to decide and examine how the economic overall performance of the Cirebon State Savings Bank Employee Cooperative primarily based totally on liquidity ratios, particularly the Current Ratio, Quick Ratio, and Cash Ratio. This look at makes use of a descriptive quantitative technique the usage of the size of liquidity ratios. The records studied had been withinside the shape of economic statements of the Cirebon State Savings Bank Employee Cooperative from 2018 to 2020. Based at the effects of the evaluation, it could be concluded that the economic overall performance of the Cirebon State Savings Bank Employee Cooperative in 2018 to 2020 primarily based totally at the Current Ratio is taken into consideration awful, that is primarily based totally at the effects of the calculation of the common Current Ratio for three years, particularly 435.61%, which continues to be a long way beneath the regulatory standard. Minister of State and Small and Medium Enterprises of the Republic of Indonesia No.06/Per./M.KUKM/V/2006 for the Current Ratio, particularly if 125% to >250% is covered withinside the awful criteria. The economic overall performance of the Cirebon State Savings Bank Employee Cooperative in 2018 to 2020 primarily based totally at the Quick Ratio is taken into consideration awful, that is primarily based totally at the effects of the calculation of the common Quick Ratio for three years, that's 427.67%, which continues to be a long way beneath the same old of the Regulation of the Minister of State and Small and Medium Enterprises Republic of Indonesia No.06/Per./M.KUKM/V/2006 for the Current Ratio, ie if 125% to >250% is covered withinside the awful criteria. The economic overall performance of the Cirebon State Savings Bank Employee Cooperative in 2018 to 2020 primarily based totally at the Cash Ratio is taken into consideration awful, that is primarily based totally at the effects of the calculation of the common Cash Ratio for three years, that's 49.01%, which continues to be a long way beneath the same old of the Regulation of the Minister of State and Small and Medium Enterprises Republic of Indonesia No.06/Per./M.KUKM/V/2006 for Cash Ratio, ie if <125% is covered withinside the awful criteria